Basic principles of viscoelastic testing. (22nd October 2020) - Carll, Timothy; Wool, Geoffrey D.
Abstract: Background: Viscoelastic testing is a method of hemostatic analysis that provides a real‐time, holistic view of ex vivo clotting. It allows for examination of both cellular and plasma protein contributions to clotting including platelet number and function, fibrin(ogen) function, and coagulation factor function. The method assesses physical clot properties during the transition of blood from a liquid to a gel state, either by measurement of clot shear modulus using physical force transduction or by measurement of clot resonance frequency using sonometric interrogation. Results are reported in a live trace, with different trace parameters reflecting different contributors to hemostasis. These reported parameters vary between testing platforms. Results: In the United States, there are several commonly used Food and Drug Administration (FDA)‐approved viscoelastic instruments available on the market. Those instruments that use sonometric clot assessment are more recently available and allow for improved portability for use near the patient's bedside. These instruments generally feature different reagent kits that allow more specific interrogation of different hemostatic pathways. Viscoelastic testing can predict the results of traditional plasma‐based coagulation assays and has the added benefit of detecting hypercoagulability and severe hyperfibrinolysis. Implementation of viscoelastic testing in many clinical settings is becoming widespread and has proven to be efficacious in reducing blood transfusion rates in many settings. An impact on overall mortality and morbidity has not yet been demonstrated. Conclusion: This article provides a narrative review of the basic principles of viscoelastic testing, including the science and technology behind the method, as well as currently available testing platforms and reagents.